THE INFLUENCE OF FASHION STYLE ON INCREASING STUDENTS’ INTERST IN LEARNING CLASS AT ELEMENTARY SCHOOL TEACHER EDUCATION (PGSD) STUDY PROGRAM QUALITY UNIVERSITY ACADEMIC YEAR 2017-2018 - RAKIYAH, SITI (Jurnal Ilmiah Aquinas, 2020)
The purpose of this study was to determine the effect of fashion styles on increasing student interest in learning at PGSD Study Program in Quality University. The method used in this research is descriptive method using a survey form. The subjects used were used students of PGSD Study Program at the University of Quality TA 2017/2018. The survey shows that the clothing styles used by students can affect their learning interest. They are more eager to go to college and go to class because one of them is the clothes they use are more contemporary, fashionable, and still new. However, it is not uncommon for students who wear clothes that are old fashioned in their interest to go to college less enthusiastic and often also have an impact on their activities in the classroom